2002
DOI: 10.3758/bf03194708
|View full text |Cite
|
Sign up to set email alerts
|

Face recognition by hand

Abstract: We investigated participants' ability to identify and represent faces by hand. In Experiment 1, participants proved surprisingly capable of identifying unfamiliar live human faces using only their sense of touch. To evaluate the contribution of geometric and material information more directly, we biased participants toward encoding faces more in terms of geometric than material properties, by varying the exploration condition. When participants explored the faces both visually and tactually, identification acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…Subjects also reported that they made no use of the eye region for tactile recognition. These subjective reports and the imaging results suggest that during tactile recognition of faces, subjects processed the faces more like other objects than like holistic face configurations (14). Even within the visual modality, face inversion impedes configural face processing (15) and results in increased activity in extrastriate cortical regions that respond more to nonface objects than to faces (16).…”
Section: Discussionmentioning
confidence: 96%
“…Subjects also reported that they made no use of the eye region for tactile recognition. These subjective reports and the imaging results suggest that during tactile recognition of faces, subjects processed the faces more like other objects than like holistic face configurations (14). Even within the visual modality, face inversion impedes configural face processing (15) and results in increased activity in extrastriate cortical regions that respond more to nonface objects than to faces (16).…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have shown that human body parts, such as faces (Kilgour & Lederman, 2002, 2006, hands, and feet (Kitada et al, 2009(Kitada et al, , 2010, and the facial expression of emotion (Lederman et al, 2007) can also be identified haptically.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the haptic exploration of stimuli that represent body parts (Kilgour & Lederman 2002, 2006Kitada, Johnsrude, Kochiyama, & Lederman, 2009;Kitada, Dijkerman, Soo, & Lederman, 2010). Additionally, none of these studies investigated specifically motor simulation evoked by the handedness recognition task, but rather the dynamics of the haptic identification of body parts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gobbini (2000, 2002) proposed that face recognition was represented in the brain as a distributed network of areas, but structured on a distinct core system centred around activity in the fusiform gyrus (Kanwisher, McDermott, & Chun, 1997;Sergent, Ohta, & MacDonald, 1992) as well as the occipital face area (e.g., Pitcher, Walsh, & Duchaine, 2011), to represent the invariant aspects of faces for identification. These areas are considered unimodal and predominantly visual (Casey & Newell, 2007;Kilgour & Lederman, 2002). Such a core system also incorporates a more anterior region of the brain, the superior temporal sulcus (e.g., Perrett et al, 1985), which represents the more changeable aspects of faces (e.g., lip movements in speech, facial expressions, eye gaze, etc.)…”
mentioning
confidence: 99%